Apical Hypertrophic Cardiomyopathy in an asymptomatic male - Hirachan, Anish; KC, Bishal (Journal of Advances in Internal Medicine, 2018)
Apical Hypertrophic cardiomyopathy is a rare variant of HCM and has a prevalence of around 15 % among HCM patients. As compared to other variants, it has a relatively benign prognosis. Predominantly prevalent in the Japanese population; it is characterized by localized hypertrophy of the LV apex as compared to other segments. It is usually silent in early stages and is manifested at an adult stage with typical ECG changes of giant T wave inversions in the precordial leads. Transthoracic echocardiography remains the mainstay of non – invasive diagnosis. We report a case of an asymptomatic elderly male who presented with the classical deep T wave inversion in ECG for which echocardiography revealed the apical variant of hypertrophic cardiomyopathy.